2009
DOI: 10.1073/pnas.0908686106
|View full text |Cite
|
Sign up to set email alerts
|

A perinuclear actin cap regulates nuclear shape

Abstract: Defects in nuclear morphology often correlate with the onset of disease, including cancer, progeria, cardiomyopathy, and muscular dystrophy. However, the mechanism by which a cell controls its nuclear shape is unknown. Here, we use adhesive micropatterned surfaces to control the overall shape of fibroblasts and find that the shape of the nucleus is tightly regulated by the underlying cell adhesion geometry. We found that this regulation occurs through a dome-like actin cap that covers the top of the nucleus. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

54
609
9
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 532 publications
(676 citation statements)
references
References 30 publications
54
609
9
4
Order By: Relevance
“…3a and Supplementary Movie 3). According to the observations of Khatau et al 18 , apical F-actin network in elongated cells was observed to become oriented with respect to the long cell axis ( Supplementary Fig. S3).…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…3a and Supplementary Movie 3). According to the observations of Khatau et al 18 , apical F-actin network in elongated cells was observed to become oriented with respect to the long cell axis ( Supplementary Fig. S3).…”
Section: Resultsmentioning
confidence: 59%
“…In addition, given recent interests on molecular linkages between apical actin filaments and nuclear membrane 18,19 , it will be interesting to investigate whether such links exist for central actin filaments and influence the force transmission process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41] For mouse osteocytes, Himeno-Ando et al observed in situ a larger nucleus/cell volume ratio in tibial bones as compared to parietal bones, 42 which suggests that there may be different functional or microenvironmental demands placed on the osteoblasts in these bones. A number of mechanisms for how changes to cell and nuclear shape may lead to changes in cell function and gene expression are being advanced.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that cytoskeletal organization and nuclear morphology are regulated by extracellular mechanical signals, such as substrate stiffness and geometry (32)(33)(34)(35)(36)(37)(38)(39)(40)(41). With the cytoskeleton physically linked to the nucleoskeleton, these extracellular mechanical signals can therefore be used to mediate changes in chromatin structure.…”
mentioning
confidence: 99%